Law Enforcement Policy on Fictitious Official Travel Orders Involving DPRD Employees in Riau Province - Febri Ningsih Nasution; Maryati Bachtiar; Davit Rahmadan (CV Edujavare Publishing, 2026)
An Official Travel Order (SPPD) is an administrative document used as the basis for official travel by government employees. However, fictitious SPPDs are often misused to disburse travel funds without actual activities, resulting in state financial losses. This study aims to analyze legal policies in investigating fictitious SPPD corruption within the Riau Provincial DPRD and assess their conformity with the principles of justice, legal certainty, and legal benefit. The research employs a normative legal method using statutory, conceptual, and case approaches. Data were collected through literature and document studies and analyzed qualitatively. The findings reveal that the fictitious SPPD scheme was conducted systematically through forged airline tickets, fabricated Fund Disbursement Notes (NPDs), falsified receipts, counterfeit stamps, and forged signatures. Investigations by the Riau Regional Police uncovered tens of thousands of fictitious travel documents, causing state losses estimated at Rp195.9 billion. Although the investigation process has generally complied with criminal procedure and anti-corruption laws, challenges remain, including complex perpetrator networks, weak internal supervision, and delays in legal proceedings. Strengthening inter-agency coordination, enhancing internal control systems, and implementing transparent digital travel administration are necessary to prevent similar corruption practices in the future.